(untitled) (Research, Society and Development, 2021)
Objective: to analyze national and international publications on strategies for monitoring the health of nursing workers. Method: integrative literature review. The searches were carried out on the bases of Latin American and Caribbean Literature in Health Sciences, Medical Literature Analysis and Retrieval System Online, Cumulative Index to Nursing and Allied Health Literature and Scopus, using descriptors. The search resulted in 687 studies. After analyzing the inclusion and exclusion criteria, 06 studies were selected. Results: six publications were found that met the study criteria, which indicated the existence only of the nursing workers’ health monitoring system tool. Conclusion: it is evident from the scarcity of studies on this subject, the need to implement technological tools to favor preventive strategies for monitoring the notifications of illnesses of nursing workers was identified.